Determinan EpidemiologisKejadian Diare Pada Anak Balita di Wilayah Kerja Puskesmas Juntinyuat - Akbar, Hairil (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2018)
Infants are a nation's investment because they are the next generation for a nation. The quality of a nation can be determined by the quality of its infants at this time. Health problems during infancy can affect growth, especially disorders in the digestive tract such as diarrhea. Diarrhea affects the absorption of nutrients for the growth of children under five and diarrhea is the leading cause of infant mortality globally. The purpose of this study was to determine the factors associated with the incidence of diarrhea in children infants in Public Health Center Juntinyuat. This was an observational analytic study using a cross-sectional study design. The population under study was entire children aged 12-59 months in Public Health Center Juntinyuat with the total population of 1882 infants. The sample consisted of 94 selected children aged 12-59 months using Simple Random Sampling. According to the result of a simple logistic regression test, there was a relationship of nutritional status with p-value 0.002 (p <0,05), the existence of the trash with p-value 0.039 (p <0,05), and the presence of wastewater disposal facilities with p-value 0,008 (p <0,05) to diarrhea occurrence in infantsÂ Keywords: Diarrhea, Nutritional Status, The Existence of The Trash, The Presence ofÂ wastewater Disposal Facilities